2007
DOI: 10.1016/j.ejvs.2006.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Varicose Veins Following Surgical Treatment: Our Experience with Five Years Follow-up

Abstract: Varicose veins recurred despite technically correct surgery confirmed on post-operative duplex ultrasonography. The likelihood of recurrence increased in the presence of SSV reflux, perforating vein incompetence and post-thrombotic deep vein incompetence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 20 publications
1
62
0
11
Order By: Relevance
“…A major problem with varicose vein treatment is the high recurrence rate 1 . Progression of disease makes a larger contribution with time, and thus the reduced early recurrence rate observed 2 years after routine preoperative duplex imaging might lessen with time.…”
Section: Discussionmentioning
confidence: 99%
“…A major problem with varicose vein treatment is the high recurrence rate 1 . Progression of disease makes a larger contribution with time, and thus the reduced early recurrence rate observed 2 years after routine preoperative duplex imaging might lessen with time.…”
Section: Discussionmentioning
confidence: 99%
“…In one recent prospective multicentre observational study paraesthesia was present in 27 per cent of legs at 6 weeks, and in the majority this persisted after 12 months 3 . Two studies reported visible recurrent varicose veins in 26 and 30 per cent of patients at 1 and 5 years respectively 3,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Like others, we believe that development of arteriovenous fistula in an early postoperative period, which had been observed in 0.2% of patients, is only possible when there is a perforation of the ablated vein into the adjacent artery caused by the local overdose of energy (46,47). It seems that absence of neovascularisation is especially important in case of SSV incompetency where the recurrence following stripping is as high as 30-52% (17,48).…”
Section: Discussionmentioning
confidence: 99%